Characterization of gene expression in apple, connected potentially to cuticular wax production - Albert, Zsolt (Acta Biologica Szegediensis, 2011)
The plant cuticle takes part in several important processes of plant’s life, e.g. controling peristomal transpiration, attenuating short-wave irradiation or discouraging the attachment of invading microorganisms. These functions are mainly fulfilled by the apolar cutin matrix and waxes of the cuticle layer on the epidermis. In Arabidopsis thaliana, the biosynthetic pathway of wax components have been mostly described, altough many steps are still unknown at this time. It is known that an endoplasmic reticulum (ER) associated elongase enzyme-complex is involved in the production of very long chain fatty acids (VLCFAs), and several other enzymes are responsible for further modifications on these molecules that build up surface waxes. We were looking for potential homologs of three Arabidopsis genes shown to be involved in wax biosynthesis (KCR1, CER2, WAX2). Primers were designed based on apple sequences which are potential orthologs of these Arabidopsis genes. Then RT-PCR experiments were carried out in order to identify the expression of these candidate genes. Our work was performed on two scab-resistant apple cultivars, the early-ripening Prima, and the late-ripening Florina. In both cases leaf, fruit peel and pulp tissues were examined. Our results show that the genes targeted have different expression levels in the tissues sampled, some show most preferential expression in the fruit peel. This means that several of the selected genes could be involved in wax-biosynthesis in the apple fruit epidermis.